Development and characterization of rat duodenal organoids for ADME and toxicology applications. (15th December 2020) - Hedrich, William D.; Panzica-Kelly, Julie M.; Chen, Shen-Jue; Strassle, Brian; Hasson, Chris; Lecureux, Lloyd; Wang, Lifei; Chen, Weiqi; Sherry, Tara; Gan, Jinping; Davis, Myrtle
Abstract: Many in vitro gastrointestinal models have been developed with the hope that they will continue to improve in their similarity to the organs from which they were isolated. Intestinal organoids isolated from various species are now being used to investigate physiology and pathophysiology. In this study, intestinal stem cells were isolated from adult rat duodenum and culture conditions were optimized to promote the growth, differentiation and development of 3D organoids. We optimized and characterized rat duodenal organoids with light and electron microscopy, immunofluorescence and notably, global mRNA expression. The metabolic capacity of these cultures was investigated using probe substrates for multiple phase I and phase II drug metabolizing enzymes and found to be in line with previous results from intestinal primary cultures and a significant improvement over immortalized cell lines. Over the course of differentiation, the gene expression profiles of the rat duodenal organoids were consistent with expected trends in differentiation to various cell lineages reflecting the duodenum in vivo . Further, incubations of these cultures with naproxen and celecoxib resulted in cytotoxicity consistent with the direct cytotoxic effects of these drugs to duodenum in vivo . Based on these characteristics, the rat duodenal organoids described herein will provide a novel platform for investigating a wide variety of mechanistic questions.